Beverages: A Requirement for Life and an Opportunity to Impact the Way We Live It - Chambers, Edgar, IV (My University, 2014)
Imagine a product that is used everyday by everyone around the world. In fact, imagine a product that must be used multiple times a day by everyone. That product is a beverage. Without beverages we cannot live. Many health practitioners recommend that adults consume approximately 2 liters of liquid daily and most of that consumption comes from beverages. Those beverages range from water to alcoholic beverages, soft drinks to coffee, tea to juice, and milk to so-called energy drinks or functional beverages. This enormous variety and consumption of beverages provides an unlimited opportunity to study product development and manufacturing, human consumption behavior, physical health and happiness, sensory impacts, public policy and a host of other important topics.[...]
Citation: Iv, C., & Edgar. (2014). Beverages: A Requirement for Life and an Opportunity to Impact the Way We Live It. Beverages, 1(1), 1–2. https://doi.org/10.3390/beverages1010001